Analyzing Ambivalence and Hybridized Individualistic Western Cultural Values in Mohsin Hamid’s Moth Smoke (Journal of Social Sciences Review, 2023)
This research explores postcolonial issues like ambivalence, cultural hybridity, mimicry, and identity crisis in Mohsin Hamid’s novel Moth Smoke. The novel presents the picture of Pakistani society surrounded by the presence of western values, cultural rifts and obsessions of materiality, and a weakening bond between the community and moral codes. Bhabha’s theory provides grounds to analyze the selected text. The wealthy characters of the novel, like Ozi and Mumtaz, are pursuing individualistic lifestyles affected by their touch with New York during their studies, while some Pakistani characters, like the drug dealer, Murad, are pursuing English as a basic language of communication only to hide their reality of low origin and stamp their authority and control over other. Ambivalence, hybridity, and mimicry of these characters are analyzed in this research. The hybridized individualistic western values lead Mumtaz to become an infidel to his husband and have extramarital affairs with Daru going against the cultural values of the Pakistani society with rigid patriarchal and sexual control over women. The space of cultural hybridity paves the way for mimicry in most of the instances and also leads to the downfall of Daru, the economically poor class friend of Ozi.
Keywords: Third World; Ambivalence, Mimicry; Hybridity; Identity Crisis; Diaspora; Family